Firms’ digital capabilities and green collaborative innovation: The role of green relationship learning - Xuemei Xie; Mengge Wang (Journal of Innovation & Knowledge)
With the growth of the digital economy and environmental concerns, an increasing number of manufacturing firms are leveraging digitalization to advance their green innovation and sustainable development. Although previous studies have examined the impact of digitalization on green innovation, few studies have investigated the effect of digital capabilities on green collaborative innovation. We theoretically classify four dimensions of firms’ digital capabilities—digital infrastructure capability, digital perception capability, digital operation capability, and digital collaboration capability—and categorize green collaborative innovation into green product collaborative innovation and green process collaborative innovation. Based on the survey data of Chinese high-tech manufacturing firms, we found that (a) four dimensions of firms’ digital capabilities have positive impacts on green product and green process collaborative innovation; (b) green relationship learning mediates the relationships among four dimensions of digital capabilities and two types of green collaborative innovation; and (c) green organizational identity positively moderates the relationships among digital infrastructure capability, digital perception capability, and digital collaboration capability and two types of green collaborative innovation; a collaborative innovation atmosphere positively moderates the relationship between green relationship learning and two types of green collaborative innovation. These findings contribute theoretically to the fields of digital capabilities and green collaborative innovation while providing new implications for managers to achieve sustainability in the digital transformation context.